KEANEKARAGAMAN LALAT (Cyclorrapha : Diptera) PADA LOKASI PENJUALAN DAGING DI PASAR KOTA PADANG - Novita, Afri; Jasmi, Jasmi; Safitri, Elza (Pendidikan Biologi, 2013)
AbstractFly is one of insects included into OrdoDiptera which has a pair of wing organized as membrane. Fly has cosmopolitan feature it means that fly life is got smooth almost in the all of the earth surface. In the world, there are 85.000 kind of flies. This study aimed to know diversity of flies in location of meats disposal of Padang city and identificationwas conducted in the Laboratory of Animal Taxonomy UnandÂ  ofÂ  Biological Science and mathematic faculty of Andalas University. This study usedÂ  twoÂ  methods, they were sweap and baiting. By using Sweap method the insecnetwas swayed twice to the left and right one in the location of meatâsdisfosal.Although, Baiting method used 3 type of bait, they are fresh fish,dray fish and mixing of ( terasi, fesh fish and dray fish). Â The research result was got3 family such as Muscidae, Calliphoridae and Sarcophaggidaethat were involvedÂ  5 species, they areMuscadomestica, Chrysomyamegacephala, Calliphorasp., Luciliasp. and Sarcophaga sp.Â Â